2006
DOI: 10.1080/02643290500483090
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between visuo-spatial attention and nonword reading in developmental dyslexia

Abstract: Focused visuo-spatial attention was studied in 10 developmental dyslexic children with impaired nonword reading, 10 dyslexic children with intact nonword reading, and 12 normally reading children. Reaction times to lateralized visual stimuli in a cued detection task showed that attentional facilitation of the target at the cued location was symmetrical in the three groups. However, dyslexics with impaired nonword reading selectively showed a lack of attentional inhibition for targets at the uncued location in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
199
2
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(228 citation statements)
references
References 56 publications
19
199
2
5
Order By: Relevance
“…The most prominent findings here were aberrant connectivity between anterior caudate and a TPJ subregion functionally connected to DAN regions such as the intraparietal sulcus, putative human frontal eye fields, and dorsolateral prefrontal cortex. Many studies have highlighted abnormalities in visuospatial attention in RD (Facoetti and Molteni 2001;Hari et al 2001;Facoetti et al 2003Facoetti et al , 2006Sireteanu et al 2005;Liddle et al 2009;Facoetti, Corradi et al 2010;Facoetti, Trussardi et al 2010). Converging evidence also suggests that difficulties in visuospatial attention are an important predictor of reading abilities (Valdois et al 2004;Shaywitz and Shaywitz 2008;Franceschini et al 2012Franceschini et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent findings here were aberrant connectivity between anterior caudate and a TPJ subregion functionally connected to DAN regions such as the intraparietal sulcus, putative human frontal eye fields, and dorsolateral prefrontal cortex. Many studies have highlighted abnormalities in visuospatial attention in RD (Facoetti and Molteni 2001;Hari et al 2001;Facoetti et al 2003Facoetti et al , 2006Sireteanu et al 2005;Liddle et al 2009;Facoetti, Corradi et al 2010;Facoetti, Trussardi et al 2010). Converging evidence also suggests that difficulties in visuospatial attention are an important predictor of reading abilities (Valdois et al 2004;Shaywitz and Shaywitz 2008;Franceschini et al 2012Franceschini et al , 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of patients with hemispatial neglect tested with centrally presented stimuli have shown degraded reports of letters in the contralateral side of nonwords but preserved reports of words (Siéroff, Pollatsek, & Posner, 1988). A recent study by Facoetti et al (2006) suggested that part of the nonword reading disability in developmental dyslexia arises from deficient deployment of spatial attention. As suggested by Facoetti et al, these results can be accommodated by a dual-route approach to word reading in which the indirect pathway for sublexical phonological assembly requires attention, whereas the direct lexical-semantic pathway is largely impervious to attentional modulation.…”
Section: Spatial Attention Word Frequency and Lexicalitymentioning
confidence: 99%
“…Furthermore, other studies which explicitly reported a phonological processing deficit based their diagnosis upon pseudoword reading difficulties (i.e., decoding or sub-lexical reading difficulties), but pseudoword reading does not only require phonological abilities but also engages visual attention (Bosse et al, 2007;Bosse & Valdois, 2009;Facoetti et al, 2006;Facoetti et al, 2010;Vidyasagar & Pammer, 2010).…”
Section: Assessing Visual and Auditory Sequential And Simultaneous Dementioning
confidence: 99%